'Fit and proper' coders? How might legal service delivery by non-lawyers be regulated?. (3rd July 2021) - Bell, Felicity; Rogers, Justine
ABSTRACT: With an upsurge of interest and investment in new legal technologies comes consideration of who is making them and whether these individuals or entities should be subject to regulation. This article looks at how such regulation might function in light of the existing regulatory regimes governing lawyers and the capacities of legal regulators. It considers the ramifications both of maintaining the existing system, or in extending some form of regulation to these new entrants to the legal services market.